DEVELOPMENT OF BANKING INTERACTION BETWEEN KAZAKHSTAN AND CHINA (Journal of actual problems of jurisprudence, 2019)
In modern economic conditions, the efficiency of the banking sector affects the development of not only the financial and economic system of the state, but also ensures the financial stability of the national economy as a whole. Considering the processes of globalization and liberalization of financial markets, as well as the growing demand of consumers of financial services, attention is being paid to the banking sector both from academics and from the management of banking institutions at various levels of government. All this causes a special interest in the banking sector of the Republic of Kazakhstan. The article explores the features of the development of the banking sector of the Republic of Kazakhstan in the conditions of the infusion of Chinese banks into the banking system. On the example of the work of Chinese banks within the country and in the global financial space, recommendations on ways to improve legislation on the banking system of Kazakhstan are made. According to current global trends in the financial market, the banking sector is entering a qualitatively new level of functioning, which leads to its analysis and identification of its structure in the Republic of Kazakhstan. The current state of the banking sector of the Republic of Kazakhstan in the context of globalization processes is analyzed. Key factors influencing the development of the banking sector of the Republic of Kazakhstan are identified. The problems and directions of development of the banking sector of the Republic of Kazakhstan at the present stage are identified. Key words: banking law, banking system, foreign banks, banking legislation.